2013
DOI: 10.1186/2050-6511-14-30
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions reported by consumers for nervous system medications in Europe 2007 to 2011

Abstract: BackgroundReporting of adverse drug reactions (ADRs) has traditionally been the sole province of healthcare professionals. In the European Union, more countries have allowed consumers to report ADRs directly to the regulatory agencies. The aim of this study was to characterize ADRs reported by European consumer for nervous system medications.MethodsADRs reported by consumers for nervous system medications (ATC group N) from 2007 to 2011 and located in the European ADR database, EudraVigilance, were analysed. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…All of the 14 observational studies were retrospective, and most commonly (8 out of 14 studies) had the aim of comparing patient and HCP ADR reports . There were five studies from Denmark , five from the Netherlands , two from the UK , one from France and one from China . Two of the Danish studies focused on analysing the Danish experience with patient ADR reporting , and three studies performed an analysis of the ADRs presented in the European ADR database EudraVigilance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the 14 observational studies were retrospective, and most commonly (8 out of 14 studies) had the aim of comparing patient and HCP ADR reports . There were five studies from Denmark , five from the Netherlands , two from the UK , one from France and one from China . Two of the Danish studies focused on analysing the Danish experience with patient ADR reporting , and three studies performed an analysis of the ADRs presented in the European ADR database EudraVigilance .…”
Section: Resultsmentioning
confidence: 99%
“…There were five studies from Denmark , five from the Netherlands , two from the UK , one from France and one from China . Two of the Danish studies focused on analysing the Danish experience with patient ADR reporting , and three studies performed an analysis of the ADRs presented in the European ADR database EudraVigilance . The majority of the studies coming from the Netherlands and the UK compared the differences between ADR reports from patients and HCPs.…”
Section: Resultsmentioning
confidence: 99%
“…Daily doses exceeding the clinical recommendation measured by means of prescription fills, further suggest misuse in a proportion of patients (112,114,211). Notably, sub-therapeutic effects of pregabalin are among the most commonly reported ADRs (212), potentially an important cause of treatment discontinuations (195).…”
Section: Pregabalinmentioning
confidence: 99%
“…A study in the EudraVigilance database, investigating the characteristics of adverse drug reactions reported by patients from 2007 to 2011, has found that pregabalin was the most frequently involved in adverse reactions related to central nervous system drugs (1 510 reports out of a total of 4 766 reports related to central nervous systems drugs). [40] The most frequently reported reaction was a lack of efficacy, and 14 reports concerned withdrawal syndrome. However, it is likely that patients who misuse or abuse pregabalin do not report this event as an adverse drug reaction, if they are not suffering of the morbid consequences of this abuse.…”
Section: Why a Pharmacoepidemiological Approach Is Needed? Pregabalinmentioning
confidence: 99%